Aktivitas Antidiabetes pada Fitokimia Cinnamaldehyde dalam Menurunkan Kadar Glukosa Darah Puasa, HbA1c, HOMA-IR, dan Meningkatkan Kadar Insulin Hewan Coba Tikus - Najah Najah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Diabetes mellitus is a metabolic disorder characterized by high blood sugar levels continuously. Insulin resistance is the main cause of type 2 diabetes mellitus, so it is very important to control it to maintain blood sugar levels. Traditional ingredients have long been used to treat diabetes. One of the traditional ingredients used is cinnamon which has been proven to have a potential effect on the management of type 2 diabetes mellitus. The content of cinnamon that has an antidiabetic effect is cinnamaldehyde which provides a distinctive taste and aroma. The method used is by analyzing journals that meet the inclusion and exclusion criteria. Articles were searched for in the search media PubMed, Science Direct, and Google Scholar. The results of analyzing the articles found were a decrease in blood glucose levels, HbA1c, HOMA-IR, and an increase in insulin levels between the blood glucose of the control group of experimental animals and the blood glucose of the group that received cinnamaldehyde intervention. The conclusion of this study is that cinnamaldehyde intervention can reduce blood glucose levels, HbA1C, HOMA-IR and increase insulin levels in the blood.